Mythological Archetypes in Marvel Film Adaptations - Szántó, Bálint (AMERICANA E-journal of American Studies in Hungary, 2019)
This paper explores the different mythological archetypes that manifest in the superhero characters of one of the most popular transmedia film franchises of recent years, the Marvel Cinematic Universe. The aim of this paper is to find connections between Marvel films and different mythologies, to trace monomythic and archetypal aspects in superhero adaptations, and to find out whether these films can serve as a modern mythology for the digital age. It builds on the idea that while people in ancient societies believed in the existence of mythological deities, people in the 21st century do not believe in the literal existence of “mythical” characters such as superheroes. However, as the origin stories of these characters involve science, they do represent humanity’s faith in scientific progress. Firstly, the theoretical background of the paper is presented, with particular emphasis on Carl Gustav Jung’s theory of archetypes and contemporary authors that work with this theory. Afterwards, three characters from the Marvel Cinematic Universe are analyzed: Captain America, Iron Man, and Hulk. Captain America is examined from the perspective of Joseph Campbell’s traditional monomyth, and Robert Jewett’s and John Shelton Lawrence’s American monomyth as well. In the case of Iron Man and Hulk, the main emphasis is on how these characters represent humanity’s feelings towards the rapid advancement of science, a motif that is present even in the mythological stories of Prometheus. Besides the analysis of mythological archetypes, it will also be discussed how the transmedia narrative of the Marvel Cinematic Universe – with stories being presented through multiple media platforms including films, TV series, and comics – is reminiscent of how Greek mythology was also told through multiple forms of media, such as epic poems, plays, and visual art. The transmedia storytelling framework and the archetypal characters that inhabit it together form a grand cultural phenomenon that influences the lives of millions of people around the globe.